Exploration and Optimization of Radiance Cascades for Real-Time Applications - GAVRAS, KYRIAKOS (My University, 2025)
This thesis introduces the fundamentals of Radiance Cascades in screen space for 2D, with more focus on the implementation of a less explored approach called Screen- Space Probes with World-Space Intervals (SPWI) to solve single shot diffuse global illumination. A conventional 3D probe grid faces significant memory constraints; however, SPWI gives a solution to capture off-screen indirect light more memory efficiently. The implementation diverges from Alexander Sannikov’s original approach in a few aspects. It employs ray-tracing instead of ray marching, which is just personal preference and it also incorporates Sannikov’s post-publication novel depth aware up-scaling method "Bilinear 3D", which he released after the release of the original Radiance Cascades paper. This work presents comparative analysis between different upscaling techniques and documents experimental approaches that, while ultimately not incorporated in the final implementation, offer valuable insights for future research. The findings contribute to the foundational understanding of this approach and establish a framework for further improvements in Radiance Cascade with SPWI for real-time rendering.
Keywords: probes; SPWI; ray-tracing; 2D; 3D; global illumination; intervals